(3GdebGdI GdeMSfjI aj JOHjQ GdUMI GdHOfjIs - (3aGVd Hf CHj GdMSf GdESQGFjdj GdScfOQj, GHf GdHQbGfjs
(3ChdgG (B:s
(3deG cGfJ GdUMI SHHkG ai GSJbGeI MGd GdEfSGf ai Ofjg hOfjGg , EP HUMI GdHOf jJecf Cf jfGd edGP s
(3BNQgG (B:s
(3aGdYbO JHOjd GdeRGM , hMdg jTai GdeQjV Hg ef GdCgGe eY ERLGA ai GdHVGYI , hbdI GdeQJHI ai gPg GdUfGYI s
(3Cdag dfGFH GdSdWfg GdYdjg HKZQ GdGScfOQjI GdeMSfi Gdedci GdfGUQi GdefUQis
(3fSNI NRGFfjI ePgHI GdWGdY hGdYfGhjfs
(3HQSe (B" (3GdNRGfI GdEeGejI GdCYXejI GdeSJYjfI GdYHGSjI SjOfG hehdGfG GdeSJYjf HGddg CejQ GdeDefjf (B"s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs